Effect of Airflow Temperature on the Formation of Initial Flame Kernel and the Propagation Characteristics of Flame - Jianzhong Li; Jian Chen; Li Yuan; Ge Hu (International Journal of Aerospace Engineering)
Using liquid RP-3 aviation kerosene as the fuel to study, the effect of airflow temperature on the formation of initial flame kernel during the ignition of spray combustion and on the propagation characteristics of flame was investigated. Combining high-speed camera and dynamic temperature acquisitions at the outlet of combustor, the internal triggering mode was used under a constant fuel flow rate and airflow velocity. This combined system simultaneously recorded the formation of initial flame kernel, flame propagation, and outlet temperature variation of combustor under different airflow temperatures. MATLAB software was used to obtain the reaction zones at different moments and to analyze the effects of airflow temperature on morphological characteristics such as flame area, perimeter-to-area ratio, maximum length-to-height ratio, equivalent mean length-to-height ratio, mass center, and centroid. According to the growth rate in flame area, the ignition process can be divided into three stages: formation of flame kernel, rapid development of flame, and stable development of flame. Airflow temperature not only affects the formation time of flame kernel but also affects the growth rate of flame area. During the development of flame, the movements of mass center and centroid are irregular, and their positions do not coincide with each other. However, the overall moving trends are consistent. With the increase of the airflow temperature, the position, where the flame kernel is gradually formed, moves closer to the center of the end face of spark plug. The force of airflow on flame is the main factor that increases the flame area and heat-release rate. Therefore, the folds around the flame edge mainly result from the stretching under the action of airflow. With the increase in airflow temperature, the heat release of the initial flame kernel increases, and the ratio of perimeter to area as a characterization parameter increases by 8%, 86%, and 33%, respectively. In addition, the maximum outlet temperature rise increased by about 53%, 73.5%, and 0.65%, respectively. Meanwhile, the maximum rate of temperature rise increased by about 42.8%, 57%, and 5.1%, respectively.